DNA Origami Nano-Sheets and Nano-Rods Alter the Orientational Order in a Lyotropic Chromonic Liquid Crystal - Bingru Zhang (Nanomaterials, 2020)
Rod-like and sheet-like nano-particles made of desoxyribonucleic acid (DNA) fabricated by the DNA origami method (base sequence-controlled self-organized folding of DNA) are dispersed in a lyotropic chromonic liquid crystal made of an aqueous solution of disodium cromoglycate. The respective liquid crystalline nanodispersions are doped with a dichroic fluorescent dye and their orientational order parameter is studied by means of polarized fluorescence spectroscopy. The presence of the nano-particles is found to slightly reduce the orientational order parameter of the nematic mesophase. Nano-rods with a large length/width ratio tend to preserve the orientational order, while more compact stiff nano-rods and especially nano-sheets reduce the order parameter to a larger extent. In spite of the difference between the sizes of the DNA nano-particles and the rod-like columnar aggregates forming the liquid crystal, a similarity between the shapes of the former and the latter seems to be better compatible with the orientational order of the liquid crystal.